A Privacy Preserving and Efficient Multi Authority – CP-ABE Scheme for Secure Cloud Communication - Porwal, Shardha; Mittal, Sangeeta (Journal of Cyber Security and Mobility, 2021)
In the cloud computing environment, Multi authority Ciphertext Policy-Attribute Based Encryption (CP-ABE) schemes are used as a key escrow free solution to securely and efficiently share data over cloud. However, the length of ciphertext in existing Multi Authority-CP-ABE schemes increases with the number of attributes in the access policy. Moreover, these schemes do not protect against dishonest attribute authorities. In this paper, a constant length ciphertext Multi Authority-CP-ABE scheme is proposed that reduces the communication overhead over the network. The scheme also prevents dishonest authority from compromising the system. Apart from this, for enhanced privacy of receivers, the access policy is communicated in hidden form. Thus, the presented scheme provides an efficient corrupt resistant, key escrow free Multi Authority-CP-ABE scheme by generating constant length ciphertext and hidden access structure. Results demonstrate the enhanced security and reduced cost of encryption and decryption by 8% and 48% respectively as compared to other existing works.